An improved single-phase asymmetrical multilevel inverter structure with reduced number of switches and higher power quality - Maamar, Alla Eddine Toubal (Institute of Electrical and Electronics Engineers, 2021)
This brief proposes an improved single-phase multilevel inverter with asymmetrical structure, consisting of ten unidirectional SiC MOSFET switches and four direct current (DC) voltage sources to produce a twenty-one voltage levels alternating current (AC). The main advantages of the proposed multilevel inverter are the simplicity and the high output power quality. The output power quality is achieved by calculating the switching angles using the half-height (HH) method, thus overcoming the problems associated with total harmonic distortion (THD) and reducing the conduction losses. Furthermore, the switching losses are reduced by using SiC MOSFET's high performance characteristics compared to their Si counterparts. To demonstrate the effectiveness of the proposed 21-level inverter, simulations using MATLAB/SIMULINK and PLECS softwares are carried out. Moreover, an experimental prototype of the inverter controlled by a C2000 Delfino-TMS320F28379D embedded board is realized to validate the results. The results indicates that THD of voltage and current are minimal, 4.2 %, and 0.3 %, respectively. The proposed multilevel inverter can be used for many applications due to its low density, low-cost and conforms to international IEEE-1547 and IEC-61727 standards.